Management and conservation program of a protected wildlife species the case of marine turtles in the Philippines - Trono, Romeo B. (1992)
The Pawikan Conservation Project (PCP) promulgated through EO 542 is the government's response to conserve and manage the dwindling marine turtle resources of the country. Currently attached to the Wildlife Division of the Protected Areas and Wildlife Bureau, the PCP is responsible for the development and implementation of conservation and protection policies, management and propagation schemes, and massive information and education programs aimed at ensuring the survival and growth of the country's remaining marine turtle population. Three major activities are implemented by the project: resource management and protection, research and investigation, and information and services extension. These activities are concentrated mainly in Turtle Islands, Tawi-Tawi which has the highest density of nesting green turtles in the country. In spite of the internal and external constraints of the PCP, its successes provide useful lessons to other conservation efforts.
Keywords: Turtles -- Conservation; Wildlife conservation; Marine resources conservation